Stratospheric and Mesospheric Winds in July-August over an equatorial station (MAUSAM, 1965)
Three successful rocket firings were made from Thumba Equatorial Rocket Methods for Research Workers Launching Station during July-August 1964 and wind data obtained, for the first time over India, in the region 16 to 0' 3mb (~28.57 km). The winds are generally found to be east northeasterly with speed 60.90 km upto 1 mb (~ 47 km). Further above, this regime appears to terminate giving place to a complex wind pattern with considerable wind shears. RAWIN observations of Trivanadrum and a few station in the same latitude belt on the days of firing were also collected. The combined results are examined in relation to (a) the extra biennial oscillation in the lower stratosphere and (b) the summer anticyclonic circumpolar vortex which is  marked in the higher stratosphere. Apart from the actual wind data, considerable weight is attached  to the character of reflection on the radarscope as observed by the Electronics Group. This gives an indication of pronounced turbulence in summer in the equatorial stratosphere in the region 0.3 to 0.15 mb (~57-63 km).